Epidemiological and Molecular Characteristics of HIV-1 Infection in a Sample of Men Who Have Sex With Men in Brazil: Phylogeography of Major Subtype B and F1 Transmission Clusters - Silva, Ágabo Macêdo da Costa e; Reis, Mônica Nogueira da Guarda; Marinho, Thaís Augusto; Freitas, Nara Rúbia de; Teles, Sheila Araújo; Matos, Márcia Alves Dias de; Carneiro, Megmar Aparecida dos Santos; Bello, Gonzalo; Stefani, Mariane Martins Araújo; Martins, Regina Maria Bringel (Frontiers in Microbiology, 2020)
This study describes HIV-1 prevalence, associated factors, viral genetic diversity, transmitted drug resistance (TDR) and drug resistance mutations (DRM) among a population of 522 men who have sex with men (MSM) recruited by the respondent-driven sampling (RDS) method, in Goiânia city, the capital of the State of Goiás, Central-Western Brazil. All serum samples were tested using a four generation ELISA and reactive samples were confirmed by immunoblotting. Plasma RNA or proviral DNA was extracted and protease/reverse transcriptase (PR/RT) regions were amplified and sequenced. HIV-1 subtypes were identified by phylogenetic inference and by bootscan analysis. The time and location of the ancestral strains that originated the transmission clusters were estimated by Bayesian phylogeographic approach. TDR and DRM were identified using the Stanford databases. Overall, HIV-1 prevalence was 17.6% (95% CI: 12.6 to 23.5). Self-declared black skin color, receptive anal intercourse, sex with drug user partner and history of sexually transmitted infections were factors associated with HIV-1 infection. Of 105 HIV-1 positive samples, 78 (74.3%) were sequenced and subtyped as: B (65.4%), F1 (20.5%), C (3.8%) and BF1 (10.3%). Most HIV-1 subtype B sequences (67%; 34 out of 51) branched within 12 monophyletic clusters of variable sizes, which probably arose in the State of Goiás between the 1980’s and 2010’s. Most subtype F1 sequences (n = 14, 88%) branched in a single monophyletic cluster that probably arose in Goiás around the late 1990’s. Among 78 samples sequenced, three were from patients under antiretroviral therapy (ART), two presented DRM. Among 75 ART naïve patients, TDR was identified in 13 (17.3%; CI 95%: 9.6 to 27.8). Resistance mutations to non-nucleoside reverse transcriptase inhibitors (NNRTI) predominated (14.7%), followed by nucleoside reverse transcriptase inhibitor (NRTI) mutations (5.3%) and protease inhibitor (PI) mutations (1.3%). This study shows a high prevalence of HIV-1 associated with sexual risk behaviors, high rate of TDR and high genetic diversity driven by the local expansion of different subtypes B and F1 strains. These findings can contribute to the understanding about the dissemination, epidemiological and molecular characteristics of HIV-1 among the population of MSM living away from the epicenter of epidemics in Brazil.